Housing Search Frictions: Evidence from Detailed Search Data and a Field Experiment - Peter Bergman; Eric Chan; Adam Kapor (Institute of Labor Economics (IZA), 2020)
This paper shows that imperfect information about school quality causes low-income families to live in neighborhoods with lower-performing, more segregated schools. We randomized the addition of school quality information onto a nationwide website of housing listings for families with housing vouchers. We find that this information causes families to choose neighborhoods with schools that have 1.5 percentage point higher proficiency rate on state exams. We use data from the experiment to estimate a dynamic model of families' search for housing on and off the website, as well as their location decisions. The model incorporates imperfect information about school quality and characterizes the bias that would arise from estimating neighborhood preferences ignoring this information problem. Having data from both the treatment and control groups allows us to estimate families' prior beliefs about school quality and each group's apparent valuation of school quality. Families tend to underestimate school quality conditional on neighborhood characteristics. If we had ignored imperfect information, we would have estimated that the control group valued school quality relative to their commute downtown by less than half that of the treatment group.
Keywords: I24; 330; housing; education; information; experiment; choice